Using Cumulative Impact Mapping to Prioritize Marine Conservation Efforts in Equatorial Guinea - Trew, Brittany T.; Grantham, Hedley S.; Barrientos, Christian; Collins, Tim; Doherty, Philip D.; Formia, Angela; Godley, Brendan J.; Maxwell, Sara M.; Parnell, Richard J.; Pikesley, Stephen K.; Tilley, Dominic; Witt, Matthew J.; et al. (Frontiers in Marine Science, 2019)
Marine biodiversity is under extreme pressure from anthropogenic activity globally, leading to calls to protect at least 10% of the world’s oceans within marine protected areas (MPAs) and other effective area-based conservation measures by 2020. Fulfilling such commitments, however, requires a detailed understanding of the distribution of potentially detrimental human activities, and their predicted impacts. One such approach that is being increasingly used to strengthen our understanding of human impacts is cumulative impact mapping; as it can help identify economic sectors with the greatest potential impact on species and ecosystems in order to prioritise conservation management strategies, providing clear direction for intervention. In this paper, we present the first local cumulative utilisation impact mapping exercise for the Bioko-Corisco-Continental area of Equatorial Guinea’s Exclusive Economic Zone – situated in the Gulf of Guinea one of the most important and least studied marine regions in the Eastern Central Atlantic. This study examines the potential impact of ten direct anthropogenic activities on a suite of key marine megafauna species and reveals that the most suitable habitats for these species, located on the continental shelf, are subject to the highest threat scores. However, in some coastal areas, the persistence of highly suitable habitat subject to lower threat scores suggests that there are still several strategic areas that are less impacted by human activity that may be suitable sites for protected area expansion. Highlighting both the areas with potentially the highest impact, and those with lower impact levels, as well as particularly damaging activities can inform the direction of future conservation initiatives in the region.